Synthesis and validation IPM technology and its economic analysis for bottle gourd (Lagenaria siceraria) - HALDER, JAYDEEP; SARDANA, H R; PANDEY, M K; KRISHNAN, NAGENDRAN; BHAT, M N (The Indian Journal of Agricultural Sciences, 2020)
The field experiment was conducted (2016-18) at Varanasi, Mirzapur and Deoria districts of Uttar Pradesh with a view to study the validation and economic viability of adaptable IPM technology in a farmers’ led approach. The IPM technology that synthesized comprising seed treatment with Trichoderma viride @5 g/kg of seed; installation of cue lure traps (MAT) for fruit flies @10/acre; raking of soil for exposing fruit fly pupae and removal of weeds, need based application of Bacillus thuringiensis @2 g/litre against Sphenerches caffer; need based spraying of Azadirachtin based neem insecticide @10 ml/litre and Imidacloprid 17.8SL @0.33 ml/litre of water for mirid bugs and whiteflies; fungicide Cymoxanyl 8WP+Mancozeb 64WP @2.5 g/litre against downy mildew were found effective in reducing the incidence of pests and minimizing the yield losses. The adoption of IPM technology, apart from lowering the incidence of major pests, also resulted in reducing the number of chemical sprays to 5–7 from 14–18 in non-IPM fields in a season with higher bottle gourd yields of 28, 29.5 and 21.7 tonnes/ha in IPM and 17.5, 18.1 and 10.9 tonnes/ ha in non-IPM fields and with marginally higher cost benefit ratio of 1:1.91, 1:2.05 and 1:2.41 in IPM than 1:1.14, 1:1.19 and 1:11, respectively in non-IPM. On an average, IPM farmers had an average net return of ₹ 145472/ha with C:B ratio of 1:2.09 as compared to the non-IPM farmers with net return of ₹ 20992/ha with a C:B ratio of 1:1.15.